MANAGEMENT OF INNOVATIVE DEVELOPMENT OF ENTERPRISES UNDER GLOBALIZATION CHALLENGES - Наталія Стоянець (Економіка та суспільство, 2024)
The meaning and theoretical aspects of the innovative development of the enterprise due to the peculiarities of the system approach in management and its formation in the agrarian sphere are defined. The innovative development management system itself is a set of interconnected elements that ensure the integrity of this system with their inherent relationships between themselves and the external environment. These relationships are aimed at achieving the goals of activities to optimize risks, costs and work results. In order to stimulate innovative development, it is proposed to join agricultural innovative digital platforms that are aimed at realizing the innovative potential of the agricultural sector by ensuring the functioning of the agricultural value chain through the commercialization of innovations and overcoming institutional barriers, as well as promoting the increase of inclusiveness of agricultural innovations through investments. A typology of the function of innovative development of modern agricultural enterprises has been formed and summarized based on the implementation of European experience, which offers stimulation and support of activities between interested parties through awareness and exchange of knowledge, the involvement of advisory, consultation and support activities, mediation through the management of conflicts between interested parties, technical support for providing advice on economic, social or technical issues, institutional support for niche innovation and fostering scaling mechanisms, building and developing capacity by providing stakeholders with increased/maintained access to resources to stimulate the innovation process.